Biostratigraphic significance of a new early sauropodomorph specimen from the Upper Triassic of southern Brazil. (17th February 2017) - Müller, Rodrigo Temp; Langer, Max Cardoso; Dias-da-Silva, Sérgio
Abstract: The Wachholz site (Caturrita Formation, Late Triassic), in Agudo, Rio Grande do Sul (RS), southern Brazil, has yielded several sauropodomorphs. This includes CAPPA/UFSM 0002, described here based on associated elements from the basalmost portion of the site. The specimen possesses a set of traits shared with typical 'prosauropods': a concave caudal margin of the trunk neural spines and a broadly convex proximal end of metacarpal V. However, it also retains some plesiomorphic features, for instance, the slender pedal digit I. Some bones closely resemble those of Unaysaurus tolentinoi, the other definitive sauropodomorph from the Caturrita Formation, an affinity corroborated by a new phylogenetic analysis. An updated biostratigraphic framework correlates the Wachholz, Água Negra (São Martinho da Serra/RS) and Botucaraí Hill (Candelária/RS) sites based on their sample of sauropodomorphs. In addition, the record of Jachaleria in the Botucaraí Hill site, a dicynodont also known from early Norian deposits of Argentina, indicates an equivalent age to deposits bearing U. tolentioni . Accordingly, a more constrained age is proposed for the Água Negra site. This is important as the early Norian marks the transition from an epoch of low sauropodomorphs representativeness to a period of extreme abundance of the group in Early-to-Middle Mesozoic ecosystems.